Towards the ideal special language translation dictionary - Mikkelsen, Hans Kristian (HERMES - Journal of Language and Communication in Business, 1991)
In order to approach the ideal special language translation dictionary, a functional approach is preferred to a structural one. Functionality can be measured by means of the relevance principle, known from the theory of relevance. Through a relevance-based analysis of prototypical special language terminological dictionaries and general language translation dictionaries it is concluded that by taking over the relevant criteria from these, it should be possible to conceive the ideal special language translation dictionary.